Unconventional Pro-inflammatory CD4+ T Cell Response in B Cell-Deficient Mice Infected with Trypanosoma cruzi - Gorosito Serrán, Melisa; Tosello Boari, Jimena; Fiocca Vernengo, Facundo; Beccaría, Cristian G.; Ramello, María C.; Bermejo, Daniela A.; Cook, Amelia G.; Vinuesa, Carola G.; Montes, Carolina L.; Acosta Rodriguez, Eva V.; Gruppi, Adriana (Frontiers in Immunology, 2017)
Chagas disease, caused by the parasite Trypanosoma cruzi, is endemic in Latin America but has become a global public health concern by migration of infected people. It has been reported that parasite persistence as well as the intensity of the inﬂammatory immune response are determinants of the clinical manifestations of the disease. Even though inﬂammation is indispensable for host defense, when deregulated, it can contribute to tissue injury and organ dysfunction. Here, we report the importance of B cells in conditioning T cell response in T. cruzi infection. Mice deficient in mature B cells (muMT mice) infected with T. cruzi exhibited an increase in plasma TNF concentration, TNF-producing CD4+ T cells and mortality. The increase in TNF-producing CD4+ T cells was accompanied by a reduction in IFN+CD4+ T cells and a decrease of the frequency of regulatory Foxp3+, IL-10+ and IL17+CD4+ T cells populations. The CD4+ T cell population activated by T. cruzi infection, in absence of mature B cells, had a high frequency of Ly6C+ cells and showed a lower expression of inhibitory molecules such as CTLA-4, PD-1 and LAG3. CD4+ T cells from infected muMT mice presented a high frequency of CD62LhiCD44- cells, which is commonly associated with a naïve phenotype. Through transfer experiments we demonstrated that CD4+ T cells from infected muMT mice were able to condition the CD4+ T cells response from infected WT mice. Interestingly, using Blimp-flox/flox-CD23icre mice we observed that in absence of plasmablast/plasma cell T. cruzi infected mice exhibited a higher number of TNF-producing CD4+ T cells. Our results showed that the absence of B cells during T. cruzi infection affected the T cell response at different levels and generated a favorable scenario for unconventional activation of CD4+ T cell leading to an uncontrolled effector response and inflammation. The product of B cell differentiation, the plasmablast/plasma cells, could be able to regulate TNF-producing CD4+T cells since their absence favor the increase of the number of TNF+CD4+ in T. cruzi infected mice.